Backbone structure of the Edwards-Anderson spin-glass model - Romá, Federico José; Risau-Gusman, S. (Amer Physical Soc, 2013)
Fil: Risau-Gusman, Sebastian Luis. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina